Algorithm for Assessing the Quality Compensation of the Skin-electrode Contact by Capacitive ECG Sensors; Electron Devices and Materials (EDM), Annual Siberian Russian Workshop; Micro/Nanotechnologies and Electron Devices (EDM) - Morenets (Morenetz) A. I. Artem Igorevich; Pavlenko B. N. Boris Nikolaevich; Lezhnina I. A. Inna Alekseevna; Boyakhchyan A. A. Arman Arturovich; Evtushenko G. S. Gennady Sergeevich (2020, 2020)
Title screen